A randomized controlled trial comparing primary tumour resection plus chemotherapy with chemotherapy alone in incurable stage IV colorectal cancer: JCOG1007 (iPACS study). (12th December 2019) - Moritani, Konosuke; Kanemitsu, Yukihide; Shida, Dai; Shitara, Kohei; Mizusawa, Junki; Katayama, Hiroshi; Hamaguchi, Tetsuya; Shimada, Yasuhiro
Abstract: It is controversial whether chemotherapy with or without primary tumour resection is effective for the patients with incurable Stage IV colorectal cancer. A randomized controlled trial, initiated in Japan in 2012, is being conducted to evaluate the survival benefit and safety of primary tumour resection plus chemotherapy compared with chemotherapy alone in asymptomatic Stage IV colorectal cancer patients with unresectable metastatic disease. Patients are randomly assigned to either chemotherapy alone or primary tumour resection followed by chemotherapy. The primary endpoint is overall survival. Secondary endpoints are progression-free survival, incidence of adverse events, proportion of patients with R0 resection and proportion of palliative surgery for the chemotherapy-alone group. This trial was registered in June 2012 with the UMIN Clinical Trials Registry as UMIN000008147 [http://www.umin.ac.jp/ctr/index-j.htm ]. In December 2017, the study protocol was amended for reducing sample size. A total of 280 patients will be enrolled over the course of 8.5 years. Abstract : This study is a randomized controlled trial to evaluate the survival benefit of primary tumour resection in asymptomatic patients with incurable Stage IV colorectal cancer.